Dietary habits, physical activity and diabetes perception among patients with type 2 diabetes mellitus in Tabuk City, Saudi Arabia - Al-Mountashiri, Nadiyah Abdullah (Electron Physician, 2017)
BACKGROUND: Medical nutritional therapy is an important aspect of diabetes care, there is an increasing awareness of breakfast skipping, late dinner and meal contents on diabetes control. AIM: To assess dietary habits, physical activity and diabetes perception among patients with type 2 diabetes. METHODS: This case-control study was conducted among patients with diabetes mellitus at the diabetes center in Tabuk City, Saudi Arabia during the period from March through June 2017. One hundred patients with type 2 diabetes and 150 control subjects were interviewed to collect demographic data regarding, breakfast skipping, late dinner intake, and fruit, vegetables, sweet food, and fast food consumption. Diabetic patients’ perception of their disease was also assessed. (If diabetes is serious, it can be prevented and reversible). Data were analyzed by SPSS version 20 using Chi-square and independent-samples t-test. RESULTS: In the present study, body mass index (BMI) (p<0.001), fast food consumption (p<0.001), fruit consumption (p=0.004), and breakfast skipping (p<0.001) were higher among patients with diabetes compared to controls. No differences were found regarding the level of exercise, smoking, late dinner intake and diabetes perception. A significant statistical difference was observed between poor and accepted control regarding sweet food intake (p=0.046) and exercise (p=0.017). CONCLUSION: Patients with type 2 diabetes had higher BMI, and were more likely to skip breakfast, consume less fast food and more fruits than control subjects. More physical activity and less sweet food consumption was observed among patients with accepted glycemic control.